2019
DOI: 10.1111/php.13154
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic Hormone and Cyclic Adenosine Monophosphate are Involved in the Control of Shark Bioluminescence

Abstract: Among Etmopteridae and Dalatiidae, luminous species use hormonal control to regulate bioluminescence. Melatonin (MT) triggers light emission and, conversely, alpha melanocyte‐stimulating hormone (α‐MSH) actively reduces ongoing luminescence. Prolactin (PRL) acts differentially, triggering light emission in Etmopteridae and inhibiting it in Dalatiidae. Interestingly, these hormones are also known as regulators of skin pigment movements in vertebrates. One other hormone, the adrenocorticotropic hormone (ACTH), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…After 30 and 45 min, cAMP concentrations of 0.18 ± 0.01 µM cm −2 and 0.17 ± 0.02 µM cm −2 were observed, respectively. Results are consistent with previous cAMP concentration measurements performed on Etmopteridae skin patches treated with various hormones 48 . Here, results demonstrated the non-involvement of cAMP in the phototransduction events.…”
Section: Absence Of Light-induced Camp Modulation Within E Spinax Phsupporting
confidence: 92%
See 4 more Smart Citations
“…After 30 and 45 min, cAMP concentrations of 0.18 ± 0.01 µM cm −2 and 0.17 ± 0.02 µM cm −2 were observed, respectively. Results are consistent with previous cAMP concentration measurements performed on Etmopteridae skin patches treated with various hormones 48 . Here, results demonstrated the non-involvement of cAMP in the phototransduction events.…”
Section: Absence Of Light-induced Camp Modulation Within E Spinax Phsupporting
confidence: 92%
“…Indeed, luminous reactions can involve either a luciferase/luciferin or a photoprotein in which a co-factor such as an ion is needed. Concerning the ILS pigment motion regulation, previous studies demonstrated the implication of various molecules in the α-MSH/ACTH and MCR pathway such as Gαs, adenylate cyclase and cAMP in the luminescence control of E. spinax 44,48,76 . Studies on metazoan melanophore granule dispersion highlighted the effector role of the cAMP-dependent protein kinase (PKA) in the MSH/MCR pathway in which the second messenger cAMP increases due to the adenylate cyclase up-regulation leading to the release of the catalytic subunit of PKA 7,88,[111][112][113] ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations